Forensic sampling practices for oil spills in the marine environment. Issue 3 (8th October 2020) - Wait, A. D.; Tuit, C. B.; Maney, J. P.
Abstract: Characterizing and studying oil spills in marine environments for forensic purposes and Natural Resource Damage Assessment often requires timely sampling of multiple, diverse matrices in a range of field conditions. The diversity of such investigations has heretofore precluded using a focused and well-defined set of sampling practices. Defining appropriate data quality objectives and utilizing quality assurance/quality control practices throughout the sampling and analysis process can help ensure sample representativeness and study data's accuracy, reliability, and usability. These are particularly important considerations when using the non-standard oil spill sampling practices sometimes required to achieve Natural Resource Damage Assessment objectives.